Analisis Simulasi Rangkaian Penyearah Setengah Gelombang Menggunakan VoltSim dengan Variasi Beban dan Kapasitor - Leonardo Manalu; Parulian Pardede; Rapael Jon Rado Pangihutan purba (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
This study aims to analyze the performance of a half-wave rectifier circuit through simulations using Voltsim with variations in load values ​​and filter capacitor capacitance. The parameters observed include the average and RMS output voltage (Vout), output current (Iout), and ripple voltage (Vripple). Simulations were performed at a 10 V input voltage with no capacitor and with varying capacitance values. The results show that the use of a capacitor significantly increases the average voltage and reduces ripple. The larger the capacitance value, the smaller the ripple voltage and the more stable the output voltage. Load variations affect the output current, where the larger the load, the smaller the current.